Bcl-XL: A multifunctional anti-apoptotic protein. (January 2020) - Li, Mingxue; Wang, Dun; He, Jianhua; Chen, Lixia; Li, Hua
Graphical abstract: Abstract: B-cell lymphoma-extra large (Bcl-XL ) is one of the anti-apoptotic proteins of the Bcl-2 family that is localized in the mitochondria. Bcl-XL is one of the key regulators of apoptosis that can also regulate other important cellular functions. Bcl-XL is overexpressed in many cancers, and its inhibitors have shown good therapeutic effects. Bcl-XL interacts with Beclin 1, a key factor regulating autophagy. Bcl-XL is essential for the survival of neurons and plays protective roles in neuronal injuries. It can promote the growth of neurons and the correct formation of neural networks, enhance synaptic plasticity, and control neurotoxicity. Bcl-XL can also promote the transport of Ca 2+ to mitochondria, increase the production of ATP, and improve metabolic efficiency. In addition, targeting Bcl-XL has shown potential value in autoimmune diseases and aging. In this review, we summarize the functions of Bcl-XL in cancer, autophagy, Ca 2+ signaling, neuroprotection, neuronal growth and synaptic plasticity, energy metabolism, immunity, and senescence as revealed by investigations conducted in the past 10 years. Moreover, we list some inhibitors that have been developed based on the functions of Bcl-XL .